2023
DOI: 10.3390/nu15204352
|View full text |Cite
|
Sign up to set email alerts
|

Adult PKU Clinics in the UK—Users’ Experiences and Perspectives

Fatma Ilgaz,
Suzanne Ford,
Michael F. O’Driscoll
et al.

Abstract: Adults with PKU require life-long management, and ideally, their care should be in a specialised adult metabolic clinic. Their outcomes and co-morbidities have received much attention, but data are lacking on their experience, satisfaction and expectations about the care they receive. This survey reports the experiences and care adults with PKU receive from specialist metabolic clinics in the UK. The online survey developed by the UK NSPKU (National Society for Phenylketonuria), was placed on the NSPKU website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Adults diagnosed with the condition require further investigation. Over the past four decades, the literature has revealed that discontinuing treatment during the developmental stages and during adulthood has adverse effects [56,57]. It is crucial to determine whether patients should continue their treatment during adulthood and which type of treatment is the most effective.…”
Section: Resultsmentioning
confidence: 99%
“…Adults diagnosed with the condition require further investigation. Over the past four decades, the literature has revealed that discontinuing treatment during the developmental stages and during adulthood has adverse effects [56,57]. It is crucial to determine whether patients should continue their treatment during adulthood and which type of treatment is the most effective.…”
Section: Resultsmentioning
confidence: 99%